ANALYSIS OF SHIVARAMA KARANTHARA’S NOVEL "RETURN TO THE SOIL" - Bharati Sangappa Gaddi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Karanthara, who enriched the Kannada literary world, was involved in many fields such as writing.. Yakshagana.. Political thought.. etc. In his writing, the novel "Return to the Soil" is a great one, expressing a message of social concern along with environmental love. The novel is a story that is woven in the regional languages ​​of Kodi, Padumunnur, Mandarthi, and Manur of the coastal areas. The roar of the sea.. the gentle breeze.. the green fields spread out in the vast plains.. the aral.. the heavy rain.. the wind.. the seashore.. the lake.. the garden.. the field.. the grove.. the grove.. all these unfold and spread before our eyes in Karantha’s words.